2005
DOI: 10.1016/j.atherosclerosis.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cardiovascular risk among smokers is related to degree of carbon monoxide exposure

Abstract: Methods: Three hundred and sixty-five men without history of cardiovascular disease (CVD) were followed over 27 years. Leg artery disease was defined as a systolic anklearm pressure ratio (ABPI) below 0.9 in either leg. Incidence of myocardial infarction (MI), stroke and deaths is based on linkage with regional and national registers. The distribution of CO in blood and expired air, respectively, was divided into quartiles.Results: There was a significant inverse relation between ABPI and CO in blood and expir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Thus, a consideration of environmental CO exposure and cardiovascular events as well as cerebral vascular events will be presented initially [28][29][30][31][32][33].…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a consideration of environmental CO exposure and cardiovascular events as well as cerebral vascular events will be presented initially [28][29][30][31][32][33].…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
“…Increased environmental presence of CO in areas with significant [29] or low [30] air pollution was associated with increased incidence of stroke, and increased workplace exposure to CO [31] in nonsmokers was associated with a 1.97-fold increase in ischemic cardiac death. Even more interesting, among tobacco smokers, the degree of increase in COHb was associated with increased cardiovascular events, stroke and death [32,33]. While supportive of the concept that CO may facilitate thrombophilia in these settings, it must be stressed that none of these settings [28][29][30][31][32][33] involved exposure to pure CO without exposure to other potential or actual products of combustion (e.g., fine particulate pollution, tobacco smoke).…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, relationships have been shown previously between COHb levels and the degree of urbanization (Radford and Drizd, 1982), and between COHb levels in donated blood and urban average ambient CO levels (Lipfert, unpublished memorandum). Further, Hart et al (2006) showed that COHb was associated with all-cause mortality even after controlling for self-reported smoking, and Hedblad et al (2005Hedblad et al ( , 2006 showed that high levels of COHb are associated with cardiovascular risk factors and mortality. However, Bono et al (2007) found that smoking effects dominated COHb findings in urban traffic policemen.…”
Section: Biomarkers and Personal Exposures It Is Widely Recognizedmentioning
confidence: 99%